Democracy fatigue : an East European epidemy - García-Rivero, Carlos (Central European University Press, 2023)
"Over the early 21st century, democracy worldwide has deteriorated significantly. At the same time, new populist forces have appeared that challenge democracies through legal reforms. The stark contrast between Eastern and Western Europe in this respect is the focus of this collection of essays.The authors consider the 2008-2012 economic crisis to be at the root of the success of the populist parties and the rise of cultural backlash against liberal values. In turn, European governments' responses to the crisis-mainly austerity measures demanded by IMF and the EU- help explain desenchantment with the European Union. These policies made the wider public feel that they were being left out of politics, and populist parties promised to return power to them. The contributors argue that polarization of the electorate can set in motion a radicalization that strengthens authoritarians at the expense of democrats. They also demonstrate that Eastern and Western Europe differ in their attitudes to the decline in quality of democracy. The studies consider how satisfied people are with the political changes they witness, and argue that seemingly more authoritarian attitudes in the East explain why people feel more satisfied with a defective democracy that empowers the populist-authoritarian political actors that they support"--